Epigenetic Changes Associated With Anthracycline‐Induced Cardiotoxicity. Issue 1 (28th August 2020) - Tantawy, Marwa; Pamittan, Frances G.; Singh, Sonal; Gong, Yan
Abstract : Advances in cancer treatment have significantly improved the survival of patients with cancer, but, unfortunately, many of these treatments also have long‐term complications. Cancer treatment‐related cardiotoxicities are becoming a significant clinical problem that a new discipline, Cardio‐Oncology, was established to advance the cardiovascular care of patients with growing cancer populations. Anthracyclines are a class of chemotherapeutic agents used to treat many cancers in adults and children. Their clinical use is limited by anthracycline‐induced cardiotoxicity (AIC), which can lead to heart failure. Early‐onset cardiotoxicity appears within a year of treatment, whereas late‐onset cardiotoxicity occurs > 1 year and even up to decades after treatment completion. The pathophysiology of AIC was hypothesized to be caused by generation of reactive oxygen species that lead to lipid peroxidation, defective mitochondrial biogenesis, and DNA damage of the cardiomyocytes. The accumulation of anthracycline metabolites was also proposed to cause mitochondrial damage and the induction of cardiac cell apoptosis, which induces arrhythmias, contractile dysfunction, and cardiomyocyte death. This paper will provide a general overview of cardiotoxicity focusing on the effect of anthracyclines and their epigenetic molecular mechanisms on cardiotoxicity.